HUBUNGAN PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN (PUAP) TERHADAP KINERJA KELOMPOK TANI DI KECAMATAN SERAWAIKABUPATEN SINTANG (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2014)
This research aim to analyse correlation program of Development Effort Agribisnis Countryside (PUAP) to Productivity Group Farmer in District Serawai and to know and analyse correlation program Development Effort Agribisnis Countryside (PUAP) to make-up of Productivity, Production, Revenue, Earnings and Cost of Farming in District Serawai. Hypothesis the raised is Anticipated farmer which accept fund of PUAP, productivity, production, revenue, earnings and cost of farmer bigger than a farmer which do not accept fund of PUAP in District Serawai. Anticipated thecorrelation program of Development Effort Agribisnis Countryside (PUAP) to make-up of farming production and earnings of farmer in District Serawai. This Research use descriptive method with quantitative approach. Data collected by dividing kuesioner to responder and with interview to elite figure and responder. Research executed in Bedaha countryside and Tunas Harapan countryside in January to March 2013. Population which is taken in this research four farmer group in Bedaha countryside and four farmer group in Tunas Harapan countryside. Taken Sampel by purposive counted 20 responder people each lot farmer. Amount of entirety sampel is 160 people. Conclusion, this research prove that farmer which accept fund of PUAP, productivity, production of farming and earnings of farmer bigger than a farmer which do not accept fund of PUAP in District Serawai. Raised by Suggestion is adjacent and tuition on an ongoing basis very expected by local farmer. Or courses training which must be passed to program receiver farmer, this is meant farmer to be able to exploit PUAP fund according to order. Keyword: Productivity, Production, Revenue, Earnings, Cost